Pedological approach on sealed soils: impacts of covering materials on soil properties in urban and peri-urban areas - Valeria Cardelli; Andrea Salvucci; Ginevra Giacomello; Stefania Cocco; Niccolò Pampuro; Luigi D'Acqui; Sara Di Leonardo (EQA)
Land consumption represents a growing environmental threat, driven by rapid urbanization and the increasing demand for space for infrastructure and housing. Among its various manifestations, soil sealing is particularly detrimental, contributing to soil degradation and the interruption of critical ecosystem services, thus highlighting the urgent need for the implementation of sustainable land management policies. De-sealing practices, in parti-cular, have gained significant traction in recent years, although preliminary studies are mandatory to evaluate the soil conditions beneath and guide the planning of necessary interventions. Therefore, this study aimed to exami-ne the pedological properties (morphological, physical, chemical, and mineralogical) of sealed soils in urban (Vallemiano neighborhood) and peri-urban (Torrette neighborhood) areas, focusing on the impact of the cove-ring materials' characteristics and uniformity on these traits. Overall, soils at both sites exhibited problems rela-ted to soil compaction, exacerbated by fine-texture classes, low nutrient levels (particularly total organic carbon and nitrogen), and the contribution of allochthonous materials. However, variations in the characteristics and uniformity of the covering materials affected the soil properties. At Torrette, the homogeneous and entirely impermeable asphalt covering prevented the interactions between the atmosphere, hydrosphere, and pedosphe-re, leading to severe anoxic conditions, mainly in the surface soil horizons. In contrast, Vallemiano presented a degraded and heterogeneous soil surface cover. Thus, water infiltration and/or capillary rise, combined with the calcareous nature of the allochthonous material, promoted the translocation and accumulation of secondary carbonates.